Recorrência, transiência e slow down para o passeio aleatório em ambiente aleatório - Weberson da Silva Arcanjo (2016)
Let {αz}z∈Z be a sequence of independent, identically distributed random variables with 0 ≤ αz ≤ 1 for all z ∈ Z. The random walk in a random environment on the integers is the sequence Xnn∈N, where X0 = 0 and, inductively, Xn+1 = Xn + 1 with probability αXn and Xn+1 = Xn − 1 with probability 1 − αXn . The objective of this work is to establish a criterion of recurrence and transience for a random walk in random environment in one dimension and study a very interesting phenomenon known as slow down which occurs when we choose a specific distribution for the environment. All the work will be based on the paper Random Walks in a Random Environment, by Fred Solomon, 1975.